Clinical and genetic analysis of a case of late onset carbamoyl phosphate synthase I deficiency caused by CPS1 mutation and literature review - Shangyu Wang; Jinglin Chen; Xiaoqi Zhu; Tingting Huang; Haifeng Xu; Guohuan Ying; Hao Qian; Wenxin Lin; Yiehen Tung; Kaleem Ullah Khan; Hu Guo; Guo Zheng; et al. (BMC, 2023)
Abstract Background Carbamoyl phosphate synthetase I defect (CPS1D) is a rare disease with clinical case reports mainly in early neonates or adults, with few reports of first onset in late neonatal to childhood. We studied the clinical and genotypic characteristics of children with childhood onset CPS1D caused by two loci mutations (one of these is a rarely reported non-frame shift mutation) in the CPS1. Case presentation We present a rare case of adolescent-onset CPS1D that had been misdiagnosed due to atypical clinical features, and further investigations revealed severe hyperammonemia (287µmol/L; reference range 11.2 ~ 48.2umol/L). MRI of the brain showed diffuse white matter lesions. Blood genetic metabolic screening showed elevated blood alanine (757.06umol/L; reference range 148.8 ~ 739.74umol/L) and decreased blood citrulline (4.26umol/L; reference range 5.45 ~ 36.77umol/L). Urine metabolic screening showed normal whey acids and uracil. Whole-exome sequencing revealed compound heterozygous mutations in the CPS1, a missense mutation (c.1145 C > T) and an unreported de novo non-frame shift mutation (c.4080_c.4091delAGGCATCCTGAT), respectively, which provided a clinical diagnosis. Conclusion A comprehensive description of the clinical and genetic features of this patient, who has a rare age of onset and a relatively atypical clinical presentation, will facilitate the early diagnosis and management of this type of late onset CPS1D and reduce misdiagnosis, thus helping to reduce mortality and improve prognosis. It also provides a preliminary understanding of the relationship between genotype and phenotype, based on a summary of previous studies, which reminds us that it may help to explore the pathogenesis of the disease and contribute to genetic counselling and prenatal diagnosis.